Non‐ablative Er:YAG laser is an effective tool in the treatment arsenal of androgenetic alopecia. (26th August 2021) - Day, Doris; McCarthy, Madison; Talaber, Iva
Abstract: Background: Up to 70% of the adult population worldwide is affected by androgenetic alopecia (AGA) hair loss. Laser therapy offers an addition or alternative to pharmaceutical and surgical treatment of hair regrowth, with non‐ablative lasers being preferred over ablative lasers in terms of safety and downtime. Combining laser therapy with different topical agents may result in better hair regrowth. Objective: The aim was to evaluate the effectiveness and safety of non‐ablative Er:YAG laser used in clinical practice, alone or in combination with other treatment modalities, in patients with both early and advanced stages of AGA. Methods and patients: Sixteen patients (7 male and 9 female) with active AGA in different stages were treated with the non‐ablative Er:YAG laser (SMOOTH TM mode, 7 mm spot size, 7.00 J/cm 2 pulse fluence, 3.3 Hz frequency) as a monotherapy or in combination with injections of platelet‐rich plasma (PRP) to the scalp, topical minoxidil, and oral supplements for the promotion and support of hair growth. Efficacy was assessed with clinical assessment of AGA grade (Ludwig scale for female / Norwood‐Hamilton scale for male) and with blind evaluation of hair quality in global photographs before and after treatment. Patients subjectively rated their satisfaction with the laser treatment on a scale from 0–3 and pain on a VAS scale from 0–10. Results: AGA grade after treatment was lower compared to baseline ( p  = 0.015 and p  = 0.125 in female and male patients, respectively). Blind evaluation indicated an improvement in hair quality in 93% of patients, either being described as much better (14%) or as better (79%), which was not correlated with age or AGA grade. The median satisfaction score was 3, and the median VAS score for pain was 2. The positive effect of the treatment on the hair quality is ongoing. No adverse reactions were reported. Conclusions: The treatment was effective in treating AGA, confirmed by a decrease in AGA grade and by blinded evaluation of global photographs. Although the possible additive or complementary effect of topical minoxidil or nutraceuticals cannot be excluded, our results suggest that the non‐ablative Er:YAG laser SMOOTH ™ mode as a monotherapy, or in combination with PRP, is an efficient and safe treatment for AGA—with a high satisfaction rate among patients regardless of patient age, AGA duration, or AGA stage.